Mortalitesi Üzerine Etkisi The Effect of Protocol Guided Therapy to Severe Sepsis Mortality - Elif Çopuroğlu; Oktay Demirkıran; Tuğhan Utku; Seval Ürkmez (Galenos Yayinevi, 2011)
Aim: The aim of our study was to investigate the effect of protocol-based therapy to the severe sepsis patients and to investigate the accordance with this protocol. Patients and Methods: According to the evidence based guideline therapy, 'Severe Sepsis Treatment Protocol' was evaluated in order to lead the therapy of severe sepsis and septic shock patients. Before starting to our study, all the intensive care stuffs were informed about the diagnostic criteria for sepsis and severe sepsis (Appendix 1). One hundred and forty eight severe sepsis and septic shock patients that underwent therapy between 2003-2004 at Sadi Sun Intensive Care Unit were investigated retrospectively to create our Retrospective Group (RG). The study group was performed on 62 severe sepsis patients, that had underwent 'Severe Sepsis Treatment Protocol' based therapy at the same intensive care unit, between June 2005- June 2006 named as Prospective Group (PG). The mortality rate was compared between two groups. The treatment compliances at the first 6 hours and 24 hours has been evaluated in group PG. Results: Mortality rate was lower in PG, but this difference was not statistically significant (p>0.204). The accordance to the protocol of the first 6 hour therapy bundle and the 24 hour therapy bundle was found %84.46 and %59.54 respectively. Conclusion: Our study shows that, protocol-based therapy decreases the mortality in severe sepsis and septic shock patients. (Journal of the Turkish Society Intensive Care 2011; 9: 90-8)